Court records management and efficient administration of justice in Nigeria (2014)
This study investigated the records management practices in Nigerian courts as they affect the administration of justice in Nigeria. Focusing particularly on the Court of Appeal and the Supreme Court of Nigeria, the population of the study comprised 634 records personnel out of which 160 were purposively sampled. The descriptive survey research method was adopted with questionnaire, interview and observation as the instruments for data collection. The study established that courts in Nigeria generated huge volumes of records predominantly in paper format but the management of the records did not follow the critical elements of records life cycle model. This had some adverse implication for efficient administration of justice in the country. Based on the findings, the paper made a case for the formulation of a comprehensive records management policy for court records and the implementation of an integrated records management programme in Nigerian courts to facilitate efficient administration of justice in Nigeria.